Analisis dan Perancangan Laboratory Information Management System (LIMS) Menggunakan Metode Total Architecture Synthesis (TAS) - Andika Bayu Saputra; Ari Cahyono (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
At present the laboratories in Colombo Yogyakarta High School have been utilized to the maximum but in the management process they are still using conventional methods and data that are not integrated either relating to administration of the laboratory, recording laboratory assets, scheduling and valuation. Recording that occurs at this time is done by using Microsoft Excel and only limited to be recorded without any synchronization and socialization to the teachers - so that it causes the use of laboratory space which is often a collision scheduling. The recording of laboratory assets is not neatly arranged so that the monitoring of assets both maintenance, replacement and repair of equipment is not well documented. This research implements the Total Architecture Synthesis (TAS) method. The total architecture synthesis method functions to determine the needs and design of business process architecture and system architecture.